Quantificação, qualificação e interação de energia sobre tecidos biológicos no processo de eletrocirúrgico de ablação - Dias Junior, Elton (2019)
Even though it is a multipurpose equipment and mandatory in a surgical center, the electrosurgical unit, or electronic scalpel, requires a larger number of research works on its operation and especially on its effects on the hospital environment. The electrical spark that develops between the active electrode and the patient’s skin, and the way it develops, is responsible for the desirable effects of an electrosurgical procedure, such as cutting, fulguration, and tissue desiccation. However, there are by-products of electric energy when it is transformed, already flowing through the biological tissue, into other forms of energy, such as radiant, sound and thermal. And these are the three forms of energy and their effects that are analyzed in this paper. The experiments simulated human skin through the use of tissues approved for these studies, such as chayote (Sechium edule) and pork (Sus scrofa dosmesticus). The electromagnetic spectrum of the electrosurgical spark was determined from ultraviolet to near infrared. The spectrum revealed the alteration of the atmosphere around the electrode, which also formed constituents of the ablated tissue, such as sodium and potassium. The spectrum also revealed that there is ultraviolet emitted at small intensities. The power in ultraviolet emission was (13 ± 5) µW when using chayote; (4 ± 2).10-1 µW when using pork and (9 ± 4).101 µW between the spark and the metal electrodes. The noise emitted by the electrosurgical spark is above the maximum limits established by the acoustic standards that regulate sound levels in operating rooms, 58 dB (A) with chayote and 67 dB with pork, measured at 50 cm from the electric spark during the cut. However, the acoustic damage determined was 2%, and is not significant during the use of the electrosurgical unit. The largest portion of transformed energy from the electric energy is thermal, approximately 56% in cuts made with chayote and 54% with pork. It is this amount of heat that heats and vaporizes the tissue, promoting ablation. Another portion of heat flows through the tissue and causes thermal damage to the tissue adjacent to the cut. Thermal damage was quantified and qualified using a thermal camera. The cuts performed were extensive and punctual. The experiments revealed that ablation of biological tissue in electrosurgical procedures is between two theoretical models aimed at explaining the way in which tissue is vaporized: the low energy model and the high energy model. The transition times between the models were determined and with chayote the transition occurred at 1.8 s, for 15% of the water contained in the ablated tissue being vaporized and with pork the transition occurred at 1.3 s and for 45% of water contained in the tissue being vaporized. Extensive cuts show the transition between these two models. After the studies of optics, acoustics and thermology, it was possible to map the transformed power fractions from the electric power.